Association of internalized stigma and insight in patients with schizophrenia. Issue 3 (3rd July 2018) - Grover, Sandeep; Sahoo, Swapnajeet; Chakrabarti, Subho; Avasthi, Ajit
ABSTRACT: Aim: To evaluate the association of internalized stigma with insight (clinical and cognitive insight) among patients with schizophrenia. Methods: 136 patients with schizophrenia were assessed on the Internalised Stigma of Mental Illness Scale (ISMIS), Positive and Negative Syndrome Scale (PANSS) and Beck Cognitive Insight Scale (BCIS). Clinical insight was assessed by PANSS-G12 item. Results: 38.2% of patients experienced internalized stigma. On the basis of mean scores of various domains of ISMIS, about two-fifths (41.9%) of participants reported stereotype endorsement, followed by discrimination experience (38.2%), stigma resistance (36.8%), social withdrawal (30.1%) and alienation (30.1%). Insight as assessed by PANSS-G12 item did not correlate significantly with stigma. Higher cognitive insight in the form of composite score (R-C index) and higher cognitive self-reflectiveness was associated with a higher level of stigma in all the domains except for stigma resistance. Higher stigma was associated with negative symptoms. Conclusion: The present study suggests that internalized stigma is highly prevalent among patients with schizophrenia. Clinical insight doesn't have any association with stigma, but cognitive insight in the form of self-reflectiveness is associated with higher stigma.